2021
DOI: 10.3390/ijerph18084362
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Lockdown on Sun Exposure of UK Office Workers

Abstract: The impact of lockdown due to the COVID-19 pandemic in April–June 2020 on UV exposure of office workers was assessed using an online survey on time spent outdoors and environmental data for different locations in the UK. Without the need for commuting and with the flexibility of homeworking, weekday time spent outdoors was higher in the 2020 lockdown than in the same period in 2017. The weekday erythema effective radiant exposure was higher in 2020 due to an additional 45 min outdoors in the late afternoon tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Thus, this study population may not be comparable to our samples, which were representative of the Austrian population and, therefore, were overall older and had a higher proportion of men. By contrast, a study [ 28 ] in UK office workers found a significant increase in TSO during the 2020 lockdown; the authors explain this surprising result by the flexibility of homeworking and extremely sunny weather in spring 2020.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, this study population may not be comparable to our samples, which were representative of the Austrian population and, therefore, were overall older and had a higher proportion of men. By contrast, a study [ 28 ] in UK office workers found a significant increase in TSO during the 2020 lockdown; the authors explain this surprising result by the flexibility of homeworking and extremely sunny weather in spring 2020.…”
Section: Discussionmentioning
confidence: 84%
“…Finally, it has to be mentioned that there is also a possible paradoxical effect of lockdown measures and telework, even increasing SUVR exposure for some categories of subjects, as recently reported [24]. In fact, many subjects felt confined to their homes/offices, and some of them possibly reacted by increasing their time outside whenever possible.…”
Section: Future Changes In Occupational Suvr Exposure Risk and Outdoo...mentioning
confidence: 81%
“…In addition to climate change, the COVID-19 pandemic and, in particular, the cultural and behavioral changes induced by the pandemic and the preventive measures taken to prevent the spread of the virus have relevantly modified the way we perceive outdoor activities. Furthermore, the pandemic has determined profound changes in work organization, e.g., highly increasing telework [22,23], even if it should be noted that this does not necessarily indicate a reduction in SUVR exposure [24]. On the one hand, the lock-down measures and the restrictions of various job activities may have somewhat reduced the risk of excessive SUVR exposure for classic outdoor professions, such as gardeners or masons, at least for some months.…”
Section: Future Changes In Occupational Suvr Exposure Risk and Outdoo...mentioning
confidence: 99%